2022
DOI: 10.1038/s41467-022-32742-x
|View full text |Cite
|
Sign up to set email alerts
|

Discrete subicular circuits control generalization of hippocampal seizures

Abstract: Epilepsy is considered a circuit-level dysfunction associated with imbalanced excitation-inhibition, it is therapeutically necessary to identify key brain regions and related circuits in epilepsy. The subiculum is an essential participant in epileptic seizures, but the circuit mechanism underlying its role remains largely elusive. Here we deconstruct the diversity of subicular circuits in a mouse model of epilepsy. We find that excitatory subicular pyramidal neurons heterogeneously control the generalization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 77 publications
0
30
0
Order By: Relevance
“…Here, we showed that commissural GCs contribute to an inter-hippocampal excitatory-to-excitatory circuit. By directly targeting pyramidal cells in the contralateral hippocampus, commissural GCs bypass several feedback and feedforward inhibitory microcircuits which could control seizures ( 47 ), suggesting that excessive activation of this cell type may facilitate the generation and/or generalization of seizures ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that commissural GCs contribute to an inter-hippocampal excitatory-to-excitatory circuit. By directly targeting pyramidal cells in the contralateral hippocampus, commissural GCs bypass several feedback and feedforward inhibitory microcircuits which could control seizures ( 47 ), suggesting that excessive activation of this cell type may facilitate the generation and/or generalization of seizures ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, using a retrograde tracer, they showed that deep subicular pyramidal cells project to the ANT while superficial subicular neurons project to the EC. 5 To assess the impact of the deep subicular projections to the ANT versus superficial projections to the EC, the authors used an optogenetic strategy. Activation of the subicular afferents that terminate in the ANT produced a proseizure effect, and inhibition of these terminals had an anti-seizure effect.…”
Section: Commentarymentioning
confidence: 99%
“…These findings were paralleled with a chemogenetic strategy in a chronic intrahippocampal CA1 kainic acid model of TLE. 5 Next, the authors explored whether the firing characteristics of deep versus superficial neurons also played a part. Using axonal calcium imaging they showed that the timing of the inputs to the ANT and EC differ.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations